TURONGGO YAKSO IN ETHNO-PHOTOGRAPHY - Perkasa, Mandira Citra; Prasetyo, Andry (Seni Media Rekam ISI Surakarta, 2018)
The idea of a photographic creation entitled Turonggo Yakso in Ethnophotography is a follow-up in addressing the disappearance of the handwritten textbook of the founder of the art of Turonggo Yakso, which contains important notes on the art of Dongkol Village society. The book contains about the history of the art of Turonggo Yakso, the design of motion, and all the rules regarding the Baritan ceremony. The purpose of the creation of this work in an attempt to re-collect records in the form of text data from the interview results of the artists Turonggo Yakso, and visual data from the show performances which are packaged in ethnophotographic photos. The process of creating this work using the ethnophotographic method supported by Dipti Desai ie Pseudo-Ethnography or